Clinical profile of disease-causing chronic airflow obstruction in tertiary care centre in Lucknow - Srivastava, Amit; Sharma, Rachit; Srivastava, Geetanjali (Asian Journal of Medical Sciences, 2023)
Background: Chronic airflow obstruction (CAO) is a chronic lung condition that interferes with normal breathing. In common practice, CAO includes chronic obstructive pulmonary disease (COPD), asthma, chronic bronchitis, and emphysema. The present study was planned to be carried out in a tertiary care center to evaluate the profile of patients with chronic airflow obstruction with an aim to establish a cause-effect relationship between various disorders with chronic airflow obstruction. Aims and Objectives: The aim of the study was to find out the prevalence of different respiratory diseases among patients diagnosed as cases of chronic airflow obstruction and to evaluate the clinical and demographic profile of patients to find out risk factors and their role in etiology of chronic obstructive airflow. Materials and Methods: We studied demographic details of the patients, smoking history, biomass exposure, and tubercular history. All the patients were clinically examined and were subjected to pulmonary function assessment. The diagnosis of the patients was made on the basis of clinical features and outcome of spirometry. COPD was graded depending on post-bronchodilator FEV1% predicted as (GOLD, 2022). Results: Among patients with chronic airway obstruction, the number of patients diagnosed as COPD was highest (68%) followed by bronchial asthma (19%) and bronchectasis (13%). Among COPD population, 48% were smokers and 20% were non-smokers. Age of patients with bronchial asthma was significantly lower than that of other groups. In the present study, proportion of males diagnosed as COPD (NS) was significantly lower (P<0.001) as compared to other groups. Conclusion: The findings in the present study highlighted that different types of CAO can affect a wide variety of population groups and share a number of risk factors; however, some demographic and clinical factors help in understanding the specific risks and type of disorder. A Change in environmental conditions and lifestyle can change the spectrum of CAO disorders.